Cultural differences in mutual gaze during face-to-face interactions: A dual head-mounted eye-tracking study - Haensel, Jennifer X.; Smith, Tim J.; Senju, Atsushi (Visual cognition, 2022)
Cross-cultural psychologists have widely discussed "gaze avoidance" as a sociocultural norm to describe reduced mutual gaze in East Asians (EAs) compared to Western Caucasians (WCs). Supportive evidence is primarily based on self-reports and video recordings of face-to-face interactions, but more objective techniques that can investigate the micro-dynamics of gaze are scarce. The current study used dual head-mounted eye-tracking in EA and WC dyads to examine face looking and mutual gaze during live social interactions. Both cultural groups showed more face looking when listening than speaking, and during an introductory task compared to a storytelling game. Crucially, compared to WCs, EA dyads spent significantly more time engaging in mutual gaze, and individual instances of mutual gaze were longer in EAs for the storytelling game. Our findings challenge "gaze avoidance" as a generalizable cultural observation, and highlight the need to consider contextual factors that dynamically influence gaze both within and between cultures.